A REVIEW OF THE TRAVEL BEHAVIOR ANALYSIS: ITS BASIS AND APPLICATION FOR DEVELOPING CITIES - Joewono, Tri Basuki; Susilo, Yusak O.; Tarigan, Ari K. M. (Jurnal Transportasi, 2008)
AbstractÂ Travel, most often viewed in theory as derived from the demand for activity participation, has almost always been modeled on the trip-based basis, i.e., the trip is treated as the unit of analysis. Attributes of a trip (e.g., its origin and destination, mode, length) have been the subjects of analysis, but not the types of activities engaged in, their durations, sequences, and timing. This paper offers a brief review of the travel behavior analysis in order to provide a better understanding and forecasting of travel behavior. The article further offers discussions on its possible applications in urban areas of developing countries where historical accumulations of transportation and communications technologies are being introduced within a short span of time, creating the environment for travel which may not be properly accounted for using the conventional trip-based models of travel demand. In addition, the dataset from Malaysia was employed as a case of study.Keywords: travel behavior, travel, demand, transportation planning, developing cities.